Control of natural convection via inclined plate of CNT-water nanofluid in an open sided cubical enclosure under magnetic field - Kolsi, Lioua; Alrashed, Abdullah A. A. A.; Al-Salem, Khaled; Öztop, Hakan Fehmi; Borjini, Mohamed Naceur (Pergamon-Elsevier Science Ltd, 2017)
A computational analysis has been performed in this work to solve three-dimensional magnetohydrodynamic natural convection in an open cubical enclosure filled with CNT-water nanofluid. The cavity is heated from left vertical wall and an inclined plate is attached inside the cavity with finite length. The study is solved for different governing parameters as Rayleigh number (10(3) <= Ra <= 10(5)), nanoparticle volume fraction (0% <= phi <= 5%), Hartmann number (0 <= Ha <= 100) and inclination angle of the fin (0 degrees <= theta <= 360 degrees). It is observed that all of these parameters can be used as passive control element for heat and fluid flow and the maximum heat transfer is formed when theta =180 degrees but minimal value of average Nusselt number is changed according to nanoparticle addition into base fluid. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Three-dimensional; CNT-water nanofluid; Inclined plate; Natural convection; Open cavity; Magnetic field